Addendum: Closed ideals of operators between the classical sequence spaces: (Bull. Lond. Math. Soc. 49 (2017) 859–876). Issue 2 (24th December 2020) - Freeman, D.; Schlumprecht, Th.; Zsák, A.
Abstract: In Theorems A and B of [1], we state that for 1 < p < ∞ the lattice of closed ideals of L ( ℓ p, c 0 ), L ( ℓ p, ℓ ∞ ) and of L ( ℓ 1, ℓ p ) are at least of cardinality c, the continuum. What our proof actually shows is that the cardinality of the lattice of closed ideals of L ( ℓ p, c 0 ), L ( ℓ p, ℓ ∞ ) and of L ( ℓ 1, ℓ p ), is at least 2 c, and thus equal to it.